2018
DOI: 10.1111/trf.15038
|View full text |Cite
|
Sign up to set email alerts
|

Spray‐dried plasma deficient in high‐molecular‐weight multimers of von Willebrand factor retains hemostatic properties

Abstract: BACKGROUND: Dried plasmas can overcome logistical barriers that prevent fresh frozen plasma (FFP) usage in acute resuscitation, but processing of these products can detrimentally alter the composition. Spraydried plasma (SpDP) from single units is deficient in high-molecular-weight multimers of von Willebrand factor (vWF), a critical facilitator of platelet adhesion and thrombus formation. We hypothesized that converting high-molecular-weight multimers to smaller-molecularweight multimers would retain vWF's ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In combination with other pre-clinical studies [12,19] that have shown SpDP to be equivalent to FFP with respect to thrombin generation and endothelial interactions, this study supports the development of inhuman studies to evaluate the efficacy and safety of SpDP in preventing and reversing trauma-related coagulopathy.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In combination with other pre-clinical studies [12,19] that have shown SpDP to be equivalent to FFP with respect to thrombin generation and endothelial interactions, this study supports the development of inhuman studies to evaluate the efficacy and safety of SpDP in preventing and reversing trauma-related coagulopathy.…”
Section: Discussionsupporting
confidence: 82%
“…Using a protocol approved by the local institutional review board, whole blood from consented healthy adult volunteers was collected into 3·2% sodium citrate (Becton, Dickinson and Company, Franklin Lakes, NJ, USA). Donor FFP was collected and shipped to the Velico (Beverly, MA, USA) for SpDP manufacturing [8,11,19]. Following collection, the whole blood (WB) was centrifuged at 200 g for 12 min after which the platelet rich plasma (PRP) was removed from the red blood cell concentrate (RBCs).…”
Section: Methodsmentioning
confidence: 99%
“…Factor levels were greater than 80% of FFP for all factors, except FXIII (74%) and vWF (60%). In vitro study of this spray-dried plasma found that, despite a reduction in high molecular weight vWF multimers, platelet adhesion was not impaired and overall clot characteristics remained within the normal range for FFP [106]. In a study of another spray-dried plasma, Spinella et al reported that, despite reductions in individual factor levels during spray-drying, thrombin generation was greater with spray-dried plasma than with FFP and liquid plasma [48], raising the possibility of increased thrombotic issues.…”
Section: Spray-dryingmentioning
confidence: 88%
“…Clotting Factor levels were greater than 80% of FFP for all factors, except FXIII (74%) and von Willebrand ristocetin cofactor activity was 60% of FFP. Using a microfluidic channel in vitro assay (BioFlux) to simulate bleeding in‐vivo, ODP plasma did not impair platelet adhesion and overall clot characteristics were normal 54, 55 . These results occurred despite a diminution in high‐molecular‐weight multimers of vWF which is a known effect of the spray drying process.…”
Section: Technology and Properties Of Spray‐dried Plasmamentioning
confidence: 94%
“…Using a microfluidic channel in vitro assay (BioFlux) to simulate bleeding in-vivo, ODP plasma did not impair platelet adhesion and overall clot characteristics were normal. 54,55 These results occurred despite a diminution in high-molecular-weight multimers of vWF which is a known effect of the spray drying process. Bercovitz et al, compared microfluidic assay clot generation (using platelets from patients with severe von Willebrand disease and resuspended in ODP and found no difference between the ODP sample and its control.…”
Section: Technology and Properties Of Spray-dried Plasmamentioning
confidence: 95%